Pendampingan Pendaftaran NIB Dan Pelatihan Media Sosial Guna Meningkatkan Ekonomi UMKM Di Kelurahan Bulak - Yanuar Tyas Suganda; Sri Muljaningsih; Mohammad Wahed (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The KKNT activities for Defending the State UPN Veteran East Java are a challenge for students who are still experiencing restrictions on movement due to the Covid19 pandemic in 2022. One of the areas targeted by the MBKM KKNT is Bulak Village with entrepreneurship and creative economy schemes. The results of the survey and field observations found partner problems, such as how to sell products that were felt to be monotonous, product designs that were of less value and less extensive marketing coverage, as well as some UMKM that did not have business legality, namely NIB. So the KKN student team from UPN formulated a work program that was expected to solve the existing problems. The target audience in this case is UMKM owners who can increase their potential through various UMKM development strategies. The results of the socialization & training activities generally went according to plan. The potential generated from service activities is that the UMKM in Bulak Village can compete, especially in controlling the local market and even exporting with digitalized and structured marketing methods with the use of social media and emphasis on product branding value.